2016
DOI: 10.1371/journal.pone.0157868
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Degree Correlation on the Size of Minimum Dominating Sets in Complex Networks

Abstract: Network controllability is an important topic in wide-ranging research fields. However, the relationship between controllability and network structure is poorly understood, although degree heterogeneity is known to determine the controllability. We focus on the size of a minimum dominating set (MDS), a measure of network controllability, and investigate the effect of degree-degree correlation, which is universally observed in real-world networks, on the size of an MDS. We show that disassortativity or negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Alternatively, it has been shown that scientific collaboration generally creates an assortative network [13,33]. Disassortative regimes have been acknowledged as an outcome of technological and biological networks [13] that embed some degree of controllability [20]. Therefore, Embrapa's scientific co-authorship network resembles networks with controls and constrains, which agrees with the findings by Zuo and Zhao [40] that more multidisciplinary institutions are not necessarily more collaborative.…”
Section: Discussion and Related Worksupporting
confidence: 75%
See 2 more Smart Citations
“…Alternatively, it has been shown that scientific collaboration generally creates an assortative network [13,33]. Disassortative regimes have been acknowledged as an outcome of technological and biological networks [13] that embed some degree of controllability [20]. Therefore, Embrapa's scientific co-authorship network resembles networks with controls and constrains, which agrees with the findings by Zuo and Zhao [40] that more multidisciplinary institutions are not necessarily more collaborative.…”
Section: Discussion and Related Worksupporting
confidence: 75%
“…It has been shown that the size of a minimum dominant set of a network, Γ, depends on µ, γ, and <k>, but not on modularity and clustering [19,20]. Decreases in Γ when µ ≤ 0 is due to the repulsion (competition) between hubs.…”
Section: Discussion and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…External control factors are expressed in many ways, such as determinacy [15], controllability [16] and stability [17]. Except that, researchers also put forward complexity [18, 19] and trade-off relationship [20] to study the topology characters for complex networks.…”
Section: Introductionmentioning
confidence: 99%
“…BA model assumes that a graph will evolve indefinitely without considering any constraint or limit on it.Apart from degree distribution, degree-degree correlation (DDC) is a network property in which nodes with similar attributes, such as degree, tend to be connected. The DDC has an important influence on the structural properties of the network and hence, used to measure stability, robustness [13], controllability of the network [14,15], spreading of diseases [16], the traffic dynamics on networks and other time varying processes. DDC is used to divide SF networks into three types: assortative, disassortative and neutral networks [17].…”
mentioning
confidence: 99%